PHYSICAL ACTIVITY AND CARDIOVASCULAR AGING: THE MECHANISM AND RECENT EVIDENCES - Theressia Handayani; Cynthia Lawrence; Ni Luh Okta Saktiadewi Tanjung; Angelia Ongko Prabowo; Stephanie Wijayanti; Luh Putu Liana Indayana Dewi; Dana Daniati; Luh Gede Wiwin Witsari Dewi; Indira Vidiari Juhanna (Sport and Fitness Journal, 2021)
ABSTRACT Successful aging in population means preserving life quality and reducing the health burden. Many factors influence the successful aging, including physiological, psychological, social, and lifestyle factors. Physical activity is an important lifestyle factor that can prevent the chronic diseases, increase longevity and survival, and also improve cognitive and physical functions in elderly. The aim of this narrative review is to explain the correlation between physical activity and successful aging. Recent systematic review showed the benefit of exercise for overall health and cardiovascular system. Physical activity promotes successful aging among middle-aged and older adults especially in the younger population. Keywords : exercise; healthy life style; cardic aging